Tracking of Borrelia afzelii Transmission from Infected Ixodes ricinus Nymphs to Mice - Pospisilova, Tereza; Urbanova, Veronika; Hes, Ondrej; Kopacek, Petr; Hajdusek, Ondrej; Sima, Radek (Infection and immunity, 2019)
Quantitative and microscopic tracking of Borrelia afzelii transmission from infected Ixodes ricinus nymphs has shown a transmission cycle different from that of Borrelia burgdorferi and Ixodes scapularisBorrelia afzelii organisms are abundant in the guts of unfed I. ricinus nymphs, and their numbers continuously decrease during feeding. Borrelia afzelii spirochetes are present in murine skin within 1 day of tick attachment. In contrast, spirochetes were not detectable in salivary glands at any stage of tick feeding. Further experiments demonstrated that tick saliva is not essential for B. afzelii infectivity, the most important requirement for successful host colonization being a change in expression of outer surface proteins that occurs in the tick gut during feeding. Spirochetes in vertebrate mode are then able to survive within the host even in the absence of tick saliva. Taken together, our data suggest that the tick gut is the decisive organ that determines the competence of I. ricinus to vector B. afzelii We discuss possible transmission mechanisms of B. afzelii spirochetes that should be further tested in order to design effective preventive and therapeutic strategies against Lyme disease.
Keywords: Ixodes ricinus; Borrelia burgdorferi komplex; lymeská nemoc; klíště; tick-borne pathogens; Mice, Inbred C3H; Lyme Disease; Nymph; Arachnid Vectors; Borrelia burgdorferi Group; myši inbrední C3H; arachnida jako vektory; nymfa; Animals; lidé; ženské pohlaví; Humans; transmission; zvířata; myši; Ixodes; Borrelia; Mice; Female; Lyme disease; Borrelia afzelii